Comparative analysis of unilateral and bilateral flexible ureterorenoscopy: a cohort multicentre study - N. K. Gadzhiev; A. D. Petrov; I. A. Gorgotsky; I. A. Labetov; V. A. Malkhasyan; V. A. Vorobyov; D. D. Shkarupa (Вестник урологии, 2023)
Introduction. Flexible ureteroscopy (fURS) with laser lithotripsy is the «gold standard» for minimally invasive treatment in patients with kidney stones less than 20 mm. Currently, there are no objective data on the efficacy and safety of bilateral interventions.Objective. To study the results of bilateral flexible URS (B-fURS) versus unilateral flexible URS (U-fURS).Materials & methods. Eighty patients prospectively enrolled in the study from July 2022 to December 2022 and was divided into 2 groups. Group 1 (n = 40) underwent U-fURS and Group 2 (n = 40) underwent B-fURS. A single stone up to 20 mm or multiple small calyx stones was an indication for the operation. The baseline values were comparable between the groups, but in the B-fURS group a 39.0% higher incidence (p > 0.002) of multiple stones and a 28.0% higher incidence (p > 0.001) of stones in the lower pole. Previous interventions were also more frequent in Group 1 (B-fURS) patients.Results. Stone-free rate did not differ (p > 0.9) between the groups and was 95.0% and 97.5%, respectively. No serious complications (p > 0.9) of Clavien III–V were observed in both groups.Conclusion. Bilateral flexible ureteroscopy is a safe and effective option for patients with bilateral kidney stones, allowing removal of stones in one anesthesia on both sides.